Digitalization and sustainability : advancing digital value - Brohman, Kathryn; Dawson, Gregory S.; Desouza, Kevin C. (Edward Elgar Publishing, 2023)
"Addressing the key research question of how organizations transform to generate new forms of public and shareholder value by leveraging digital technology, expert contributors provide a deep dive into a diverse variety of business models from around the globe. The book also provides a timely focus on multisector ecosystems where organizations have limited, if any, ability to operate using monopolistic and/or command-and-control mechanisms. Digitalization and Sustainability examines how high-tech and information-intensive industries have brought to light the fundamental tenants of 'business ecosystems', illustrating how in other industries, the opportunities and practices for advancing performance by competing and cooperating in a network of organizations is less understood. It reviews how, in the context of technology management, digital value brings to light the reality that managers in specific organizations need to adopt a new set of cooperative and competitive practices. Chapters offer insights on ways to help these managers navigate an ecosystem to generate value for their own organization while enabling the larger system to evolve and improve. This book will be a valuable resource for students and faculty in the fields of information systems, public management, public policy and technology management. Researchers investigating digital transformation efforts using multiple theoretical lenses and looking for a wide range of research methodologies will find this book informative and instructive"--